Gradual martensitic transformation of B2 phase on TiCu-based bulk metallic glass composite during deformation. (August 2016) - Hong, S.H.; Kim, J.T.; Park, H.J.; Kim, Y.S.; Suh, J.Y.; Na, Y.S.; Lim, K.R.; Park, J.M.; Kim, K.B.
Abstract: In this study, we investigate the progress of stress-induced martensitic transformation depending on the stress state on TiCu-based bulk metallic glass composite via systematical transmission electron microscopy analysis. On the stage of elastic deformation (before yielding), the martensitic transformation from austenite B2 phase to martensite B19′ phase occurred from interface between B2 particle and amorphous matrix with ∼50 nm region. Just after yielding, the martensitic transformed region was extended toward B2 particle with distance of ∼130 nm from the interface. Moreover, the deformation twinning of martensite B19′ phase in martensitic transformed region was also observed. When 1% plastic deformation occurred, the martensitic transformed region reached up to ∼600 nm. Based on these results, it is believed that the high level of stress can be concentrated around the interface due to the elastic mismatch of B2 and amorphous phases. As a result, structural gradient morphology originated from phase transition was formed into the B2 particle during early stage of deformation. Graphical abstract: Highlights: Gradual martensitic transformation occurs depending on the stress state. Martensitic transformation of B2 phase happens even before yielding. Stress concentration on interface is due to elastic property mismatch.